The Learning Curve of Unilateral Biportal Endoscopic (UBE) Spinal Surgery by CUSUM Analysis - Chen, Lei; Zhu, Bin; Zhong, Hua-zhang; Wang, Yi-guo; Sun, Yi-song; Wang, Qi-fei; Liu, Jian-jun; Tian, Da-sheng; Jing, Jue-hua (Frontiers in Surgery, 2022)
OBJECTIVE: To assess the learning curve of unilateral biportal endoscopic technique for the treatment of single-level lumbar disc herniation using CUSUM method analysis. METHODS: A retrospective analysis was conducted to assess 97 patients’ general condition, operation time, complications and curative effect of single segmental UBE surgery performed by a spinal surgeon in the early stage of his career. The learning curve of operation time was studied using a CUSUM method, and the cut-off point of the learning curve was obtained. RESULTS: The CUSUM assessment of operation time, revealed the learning curve was the highest in 24 cases, which indicated that about 24 cases were needed for surgeons to use UBE technique to reach proficiency. In the learning stage (1-24 cases), the operation time was 120.3±43.8 minutes. In the skilled stage (25-97 cases), the operation time was 90.5±27.8 minutes. CONCLUSIONS: About 24 cases of single segmental UBE operation are needed to master UBE technique.